The Effect of Cultivation Techniques on Soil Characteristics and Bambara Groundnut Production - Al Hamdi, Muhammad Fauzan Farid; Kusumawardani, Mawar; Astuti, Hanifah Dwi; Pruwita, Adika Trias (Journal TECHNO, 2023)
The potential of bambara groundnut (Vigna subterranea (L.) Verdcourt) as a source of protein is relatively high, but the production is relatively low. Efforts that can be made to increase production include modifying cultivation techniques. The aim of this research is to determine the effect of cultivation techniques on soil characteristics and bambara groundnut production, as well as to determine the correlation between production variables and soil characteristics. This research was conducted in Dukuh Tanjung, Umbulmartani Village, Sleman district. The design used was a Randomized Complete Block Design with one factor and three replications/blocks. The factors applied are 2 cultivation techniques: using beds and without using beds. The variables observed in this research include pod yield variables and soil character analysis. The bambara groundnut cultivation technique with beds produces a lighter density per mass than the cultivation technique without beds. The element P (phosphorus) content in the soil is an element that has a real positive correlation with all yield variables. The dust fraction is the soil fraction that is most significantly negatively correlated: negatively correlated with the number of pods per plant, dry pod weight per plot, N content and K content in the soil.